2021
DOI: 10.1172/jci.insight.145632
|View full text |Cite
|
Sign up to set email alerts
|

Striatal TRPV1 activation by acetaminophen ameliorates dopamine D2 receptor antagonist–induced orofacial dyskinesia

Abstract: Antipsychotics often cause tardive dyskinesia, an adverse symptom of involuntary hyperkinetic movements. Analysis of the U.S. Food and Drug Administration Adverse Event Reporting System and JMDC insurance claims revealed that acetaminophen prevents the dyskinesia induced by dopamine D2 receptor antagonists. In vivo experiments further showed that a 21-day treatment with haloperidol increased the number of vacuous chewing movements (VCMs) in rats, an effect that was inhibited by oral acetaminophen treatment or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Furthermore, several studies have found that haloperidol treatment causes dopamine receptor hypersensitivity by inhibiting the dopamine D2 receptors speci cally located in the striatum. As a result, there is an increase in oxidative stress that leads to neurodegeneration [5,34]. Another study reported higher levels of free radical formation in TD patients compared to those who do not have the illness [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have found that haloperidol treatment causes dopamine receptor hypersensitivity by inhibiting the dopamine D2 receptors speci cally located in the striatum. As a result, there is an increase in oxidative stress that leads to neurodegeneration [5,34]. Another study reported higher levels of free radical formation in TD patients compared to those who do not have the illness [35].…”
Section: Discussionmentioning
confidence: 99%
“…BP cases were defined according to the ICD10 system, based on BP-related symptoms ( Supplemental Table 3 ). To produce a time-series analysis of MarketScan data, the software packages “survival” ( 13 ) and “MatchIt” ( 14 ) in R software v4.1.2 and RStudio (2022.07.1 Build 554 software, R Foundation for Statistical Computing) were used as previously described ( 9 ). The incidence of BP associated with the use of DPP4 inhibitors was first evaluated via Poisson regression analysis, and the obtained results were expressed as incidence rate ratio (IRR), along with the 95% confidence interval (CI) and Z scores.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, data obtained from the FDA Adverse Event Reporting System (FAERS) database, which is the largest self-reported adverse event database, were analyzed to identify concomitant drugs that reduce the incidence of adverse events ( 7 , 8 ). Furthermore, the causal relationships between concomitant drug use and incidence of adverse events have also been demonstrated using insurance claims databases ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, they successfully showed that acetaminophen and the acetaminophen metabolite AM404 are valid options for alleviation of TD. They also showed that TRPV1 is a crucial component in the mechanism of acetaminophen action since the anti-dyskinetic effect was lost in the TRPV1 knock-out animals if compared to wild-type rats ( Nagaoka et al, 2021 ). Furthermore, in a monkey model of TD induced by haloperidol, monkeys treated with haloperidol without TD had a higher expression of the transcription factor NUR77.…”
Section: Preclinical Studies Of Tardive Dyskinesia Developmentmentioning
confidence: 99%